Occupational status and health transitions - G. Brant Morefield; David C. Ribar; Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2011)
We use longitudinal data from the 1984 through 2007 waves of the Panel Study of Income Dynamics to examine how occupational status is related to the health transitions of 30 to 59 year-old U.S. males. A recent history of blue-collar employment predicts a substantial increase in the probability of transitioning from very good into bad self-assessed health, relative to white-collar employment, but with no evidence of occupational differences in movements from bad to very good health. These findings are robust to a series of sensitivity analyses. The results suggest that blue-collar workers wear out faster with age because they are more likely, than their white-collar counterparts, to experience negative health shocks. This partly reflects differences in the physical demands of blue-collar and white-collar jobs.
urn:nbn:de:101:1-201104113559
Keywords: I12; J24; 330; occupations; physical demands; health; Arbeitskräfte; Sozialer Status; Angestellte; Arbeiter; Gesundheit; Gesundheitsvorsorge; USA